2009
DOI: 10.1039/b913344e
|View full text |Cite
|
Sign up to set email alerts
|

Cationic rhodium(I)/bisphosphine complex-catalyzed cyclization of 1,6-diynes with carboxylic acids

Abstract: A cationic rhodium(I)/bisphosphine complex catalyzes carboxylative cyclizations of 1,6-diynes, leading to cyclic dienyl carboxylates, in high yields with high chemo-, regio-, and stereoselectivities under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…During their study of the ruthenium‐catalyzed decarboxylative cyclization of 1,6‐diynes, Saá and co‐workers found that several 1,6‐ and 1,7‐diynes underwent hydrocarboxylative cyclization in acetic acid as the solvent to afford exocyclic 1,3‐dienyl acetates in various yields and regio‐ and stereoselectivities 16. Later, Tanaka and co‐workers developed a rhodium‐catalyzed regio‐ and stereoselective hydrocarboxylative cyclization of unsymmetrical 1,6‐ and 1,7‐diynes that possess both internal and terminal alkynes, affording similar exocyclic 1,3‐dienyl carboxylates 17. In contrast to these examples, a different type of ruthenium‐catalyzed hydrocarboxylative transformation of terminal 1,6‐diynes to cyclohexenylidene enol esters was reported by Lee and co‐workers 18.…”
Section: Resultsmentioning
confidence: 99%
“…During their study of the ruthenium‐catalyzed decarboxylative cyclization of 1,6‐diynes, Saá and co‐workers found that several 1,6‐ and 1,7‐diynes underwent hydrocarboxylative cyclization in acetic acid as the solvent to afford exocyclic 1,3‐dienyl acetates in various yields and regio‐ and stereoselectivities 16. Later, Tanaka and co‐workers developed a rhodium‐catalyzed regio‐ and stereoselective hydrocarboxylative cyclization of unsymmetrical 1,6‐ and 1,7‐diynes that possess both internal and terminal alkynes, affording similar exocyclic 1,3‐dienyl carboxylates 17. In contrast to these examples, a different type of ruthenium‐catalyzed hydrocarboxylative transformation of terminal 1,6‐diynes to cyclohexenylidene enol esters was reported by Lee and co‐workers 18.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, strict removal of water traces did not show an improvement on the reaction outcome, and the desired product and byproducts ratios remained unchanged (Table , entry 12). Because the formation of five-membered ring 1,3-diene 6 byproducts would be the result of a rhodium-catalyzed carboxylative cyclization of diyne 2a in the presence of the released competitive carboxylic acid in the medium, as already reported by Tanaka and co-workers (see mechanistic discussion for more details, Scheme ), the latter could be suppressed by changing the nature of the indenone derivative 4 . Unfortunately, the use of indenone 4b as precursor of less acidic pivalic acid in the medium after the sequence [2 + 2 + 2] cycloaddition/β-elimination did not show any improvement (Table , entry 13).…”
mentioning
confidence: 73%
“…Final reductive elimination and following rearomatization would furnish the corresponding fluorenone 1 . Carboxylative cyclizations of 1,6- and 1,7-diynes using carboxylic acids have been previously accomplished under rhodium catalysis and these reactions would involve the addition of a O–H bond on a metallacyclopentadiene intermediate. Under our reaction conditions, the released carboxylic acid would react with the shared rhodacyclopentadiene intermediate A to form a novel intermediate E bearing a carboxylate ligand after protonation of the metallacycle.…”
mentioning
confidence: 99%
“…However, we have already reported that rapid aromatization through the selective [2+2+2] cycloaddition of the enol double bond and subsequent elimination of methacrylic acid proceeds in the reaction of a 1,6‐diyne and vinyl methacrylate, catalyzed by the cationic rhodium(I)/ rac ‐binap complex (Scheme ) 8c. 10 Therefore, the amide‐linked 1,5‐dienes 2 were selected for this cascade reaction.…”
Section: Methodsmentioning
confidence: 99%